TEORI KOMUNIKASI ORGANISASI MODERN DALAM PRAKTIK AMSI SULSEL MENGAWAL PROFESIONALISME PERS - Dian Muhtadiah Hamna (Jurnal Dakwah Tabligh, 2021)
The Indonesian Cyber Media Association (AMSI) of South Sulawesi was born along with the establishment of the Central AMSI in 2017. This organization was formed to strengthen the quality of cyber media journalistic products in accordance with the code of ethics and improve cyber media governance in Indonesia. The management of this media organization in order to become professional cannot be separated from the communication process among its members. So the authors conducted research on how to apply Modern Organizational Theory in AMSI South Sulawesi. The research method used is qualitative research, namely research that is descriptive and uses analysis. The author conducted in-depth interviews with three South Sulawesi AMSI administrators as informants. The results of the study stated that AMSI Sulsel always showed attitudes and actions to realize the professionalism of the press and journalistic work in online media. Professional editorial work, especially those that have an effect on social improvements in the community, always correlates with the sustainability of the media industry and its business.